2013
DOI: 10.11648/j.ajpa.20130101.12
|View full text |Cite
|
Sign up to set email alerts
|

A plasma Formation in Pulsed Coaxial Gun at Continuously Filling Regime

Abstract: In work presented the results of researches of plasma flow formation and propagate in the electrodynamics pulsed gun. Experimental researches carried out on the basis of pulse plasma accelerator CPU-30 with a coaxial symmetric geometry electrodes. It was shown, that structure of the flow significantly depends on initial operating pressure of working gas, and specify for "continuously filled" regime. The data on dynamics of plasma acceleration, obtained in previous studies was refined. The role of plasma intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The criterion for the possibility of implementing this is a comparative analysis of the physical compatibility of the complex parameters of the two objects of study. Four parameters are considered in comparison (table 1): the physical mechanism of the process, the composition of the working substance, the presence of a neutron output, parametric characteristics of the plasma generated during the process [1][2][3].…”
Section: The Theoretical Partmentioning
confidence: 99%
“…The criterion for the possibility of implementing this is a comparative analysis of the physical compatibility of the complex parameters of the two objects of study. Four parameters are considered in comparison (table 1): the physical mechanism of the process, the composition of the working substance, the presence of a neutron output, parametric characteristics of the plasma generated during the process [1][2][3].…”
Section: The Theoretical Partmentioning
confidence: 99%
“…The CS velocity is estimated by dividing the distance (2 cm) by the difference in the time between the two peaks (detected by the two probes). 23,29,34) The CS velocity is estimated from the two magnetic probes signals which are shown in Fig. 6 at the operating conditions of 0.5 Torr helium gas pressure and 5 kV charging voltage.…”
Section: ( ) /mentioning
confidence: 99%
“…21,22) The plasma formation has been investigated in a pulsed coaxial plasma by means of the magnetic field distribution along the electrodes using the magnetic probe measurements. 23) They also reported that the velocity in the exit of the electrode is high. Additionally, they reported that the initial gas pressure (at least on the range from 0.1 to 1 Torr) has no effect on the average flow velocity but it has a significant influence on the dynamics of the magnetic field inside the electrode space.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation